Exopolysaccharides from milk fermented by lactic acid bacteria enhance dietary carotenoid bioavailability in humans in a randomized crossover trial and in rats. Issue 4 (21st February 2020) - Morifuji, Masashi; Ichikawa, Satomi; Kitade, Masami; Fukasawa, Tomoyuki; Asami, Yukio; Manabe, Yuki; Sugawara, Tatsuya
ABSTRACT: Background: Dietary supplementation with carotenoids can have beneficial health effects, but carotenoids are poorly absorbed. Objectives: We aimed to evaluate how milk fermented by lactic acid bacteria affects dietary carotenoid bioavailability in humans and rats and to investigate mechanisms by which active components in milk fermented by Lactobacilli enhance dietary carotenoid absorption. Methods: Male rats ( n  = 8/group) were administered β-carotene or β-carotene + fermented milk. Rats ( n  = 6/group) were also pretreated with ezetimibe, a cholesterol absorption inhibitor, to investigate β-carotene transport mechanisms. In humans, 3 studies were conducted using a randomized crossover method. Subjects ( n  = 16/study) consumed a vegetable (carrot, tomato, or spinach) drink alone or with a fermented milk drink. Blood samples were collected at various time points after consumption. Results: In rats, the serum β-carotene area under the concentration–time curve (AUC) was significantly higher for the β-carotene + fermented milk than for β-carotene only. A significant correlation ( r  = 0.83, P  < 0.001) between the exopolysaccharide (EPS) content of fermented milk and serum β-carotene AUC was observed. Ezetimibe treatment did not suppress elevations in serum β-carotene concentrations induced by fermented milk ingestion. In humans, the incremental area under the concentration–time curve (iAUC) for β-carotene in the plasma triacylglycerol-rich lipoprotein (TRL) fraction was significantly (1.8-fold, range: 0.6–3.9) higher when carrot + fermented milk was consumed compared with carrot drink alone. A significantly (6.5-fold, range: 0.04–7.7) higher iAUC for lycopene in the plasma TRL fraction was observed for subjects who consumed tomato + fermented milk compared with tomato drink alone. A significant increase in plasma lutein in all fractions was observed after consumption of spinach + fermented milk, but not with spinach drink alone. Conclusions: Co-ingestion of β-carotene and fermented milk significantly increased dietary β-carotene bioavailability in humans and rats. EPSs could affect the physical properties of fermented milk to enhance dietary β-carotene absorption mediated by simple diffusion mechanisms. These findings may be relevant for methods to increase dietary carotenoid bioavailability. This trial was registered at umin.ac.jp/ctr as UMIN000034838, UMIN000034839, and UMIN000034840.